PENGARUH KEPERCAYAAN, KEMUDAHAN DAN RESIKO TERHADAP KEPUTUSAN PEMBELIAN MENGGUNAKAN METODE PEMBAYARAN SHOPEE PAYLATER DI WILAYAH KOTA SURAKARTA - Essen Atwandira Putri; Ahmad Husin; Maria G. Sukamdiani (JURNAL WIRANOMIKA, 2023)
The Effect of Trust, Convenience, and Risk on Purchasing Decisions Using the Shopee Paylater Payment Method in the Surakarta City Region. This study aims to determine the effect of Trust, Convenience and Risk partially on Purchase Decisions using the Shopee Paylater payment method in the Surakarta area. To determine the effect of Trust, Convenience and Risk simultaneously on Purchasing Decisions using the Shopee Paylater payment method in the Surakarta area. To find out which variables have the most dominant influence on Trust, Convenience, and Risk on Purchase Decisions using the Shopee Paylater payment method in the Surakarta area.Based on the results of the study, the regression results were obtained: Y = 1.187+ 0.893 ð‘‹1 + 0.216 ð‘‹2 + 0.187ð‘‹3. Based on statistical data analysis, the indicators in this study are valid and the variables are reliable. Individually, the variable that has the greatest influence is the Trust Variable with a regression coefficient of 0.893, followed by the Ease Variable with a regression coefficient of 0.216 and the Risk Variable with a regression coefficient value of 0.187. Hypothesis testing using the t test states that partially the independent variables consisting of Trust (X1), Ease (X2) and Risk (X3) affect the dependent variable in the form of Purchase Decision (Y) and hypothesis testing using the F test shows that simultaneously there is a significant influence between the variables Trust (X1), Ease (X2) and Risk (X3) on Purchasing Decisions (Y). Adjusted R Square figure of 0.926 (92.6%) indicates that the purchasing decision variable can be explained by the variables Trust (X1), Ease (X2) and Risk (X3), and the remaining 7.4% is influenced by other variables and is not included in analysis of this research.Â Â Keywords : Trust, Convenience, Risk, Purchasing Decisions